Elevated high-sensitivity C-reactive protein among apparently healthy adults with concomitant prediabetes and latent tuberculosis infection in Nigeria - Akinshipe, Benson O.; Yusuf, Edirin O.; Ehiaghe, Alfred F.; Egunjobi, Tunde O.; Yusuf, Opeoluwa A. (International Journal of Research in Medical Sciences, 2021)
Background: The increasing prevalence and convergence of type 2 diabetes mellitus (DM) and active tuberculosis (TB) comorbidity, especially in adults in the lower-and middle-income countries, demand new approaches to control the ‘syndemic’. Consequently, we set out to investigate the possibility of early detection of prediabetes mellitus and/or latent tuberculosis infection using novel method. Methods: This was a case-control study of 105 adults classified into 4 groups: Healthy Community Controls (HCC, n=30); Prediabetes mellitus (PDM, n=25); Latent Tuberculosis Infection (LTBI, n=23); Individuals with Prediabetes mellitus+Latent Tuberculosis Infection (PDM+LTBI, n=27). Sera collected were assayed for high-sensitivity C-reactive protein (hs-CRP) using the ultra-sensitive Human high sensitivity C-reactive protein ELISA Kit (Melsin Medical Co., Ltd, China). Other ancillary tests and measurements done include Erythrocyte Sedimentation Rate, serum Glycated-hemoglobin (HbA1c), Interferon-gamma (INF-ϒ) and Waist circumference. Results: A total of 88 (83.8%) of the enrolled participants had full complement of results and were included in the analysis of four study groups: HCC (n=25), PDM (n=21), LTBI (n=19) and PDM+ LTBI (n=23). With respect to the serum biomarkers, isolated PDM and LTBI cases recorded significantly higher HbA1c (%) and INF-ϒ positivity respectively. Predictors of PDM+LTBI show statistically significant higher tertile (T3), representing elevated hs-CRP levels, (OR=6.50, 95% CI=4.83-22.39, p=0.0037). Conclusions: This study revealed that persons harboring the two associated asymptomatic conditions, PDM + LTBI have higher inflammatory state detectable by assaying the biomarker, hs-CRP, which could be used for ‘one-time bi-directional targeted screening’ for PDM in LTBI and vice versa.